ANTI-INFLAMMATORY ACTIVITY OF METHANOLIC EXTRACT OF HIBISCUS PLANTIFOLIUS - K, Sowjanya; S, Swati; K, Supriyanka; Sk, Rajiya; B, Meena; P, Poojitha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present study was to carry out anti-inflammatory activity of methanolic extract of Hibiscus plantifolius (MEHP) belonging to the family Malvaceae. Methods: The shade dried stem part of H. plantifolius (1 kg) was powdered and extracted with methanol using soxhletion. The extract was concentrated using rotary evaporator under reduced pressure at 40Â°C, till free from the solvents and thereby providing crude methanol extract which was subsequently employed for further studies. Anti-inflammatory effect was studied by carrageenan-induced paw edema model in rats at dose level of 50, 150, and 300 mg/kg. Acute oral toxicity study was also studied. Results: The results indicate that MEHP, 300 mg/kg, exhibited significant inhibition (p<0.001) of increase in paw edema at 4th h. Conclusion: The results of the experimental study confirmed that MEHP possesses significant anti-inflammatory activity.